Prevalencia de distemper canino en la fundación Latacunga Animalista. - Herrera Panchi, Diana Jadira (2021)
The present research work was carried out in the city of Latacunga, Cotopaxi province, the objective was to determine the prevalence of Canine Distemper in the Latacunga Animalista FLANI Foundation by means of the ELISA diagnostic method using blood samples. FLANI is an establishment that houses abandoned and abused domestic canines, they must be free of diseases to be adopted. For this reason, it is necessary to investigate infectious diseases in this case Canine Distemper. The research was of a descriptive percentage type, the real prevalence was 6.24%, in 30 domestic canines existing in the shelter. In relation to the sex variable, it was found that of the 30 domestic canines, 22 are female, showing 2 positive cases and 8 negative males, with a risk ratio, whose confidence interval includes 1, showing that sex is not associated (p> 0.05) upon presentation of the Canine Distemper. In the age variable from 2 to 3 years with a population of 14 domestic canines, a positive case was obtained and in the range of 4 to 5 years with a population of 16, a positive case was also found, the risk ratio in this case represents values that include 1, showing that there is no significant difference (p> 0.05), therefore, age does not influence the presentation of the disease. It is concluded that the real prevalence in this shelter is low, however, attention must be paid frequently to the domestic canines that enter and that are inside the shelter, so as not to spread possible diseases, for this a sanitary program was developed for the entry of domestic canines to shelters.